Bile salt export pump-reactive antibodies form a polyclonal, multi-inhibitory response in antibody-induced bile salt export pump deficiency - Stindt, Jan; Engelmann, Guido (Hepatology, 2016)
Progressive familial intrahepatic cholestasis type 2 (PFIC-2) is caused by mutations in ABCB11, encoding the bile salt export pump (BSEP). In 2009, we described a child with PFIC-2 who developed PFIC-like symptoms after orthotopic liver transplantation (OLT). BSEP-reactive antibodies were demonstrated to account for disease recurrence. Here, we characterize the nature of this antibody response in 7 more patients with antibody-induced BSEP deficiency (AIBD). Gene sequencing and immunostaining of native liver biopsies indicated absent or strongly reduced BSEP expression in all 7 PFIC-2 patients who suffered from phenotypic disease recurrence post-OLT. Immunofluorescence, western blotting analysis, and transepithelial transport assays demonstrated immunoglobulin (Ig) G-class BSEP-reactive antibodies in these patients. In all cases, the N-terminal half of BSEP was recognized, with reaction against its first extracellular loop (ECL1) in six sera. In five, antibodies reactive against the C-terminal half also were found. Only the sera recognizing ECL1 showed inhibition of transepithelial taurocholate transport. In a vesicle-based functional assay, transport inhibition by anti-BSEP antibodies binding from the cytosolic side was functionally proven as well. Within 2 hours of perfusion with antibodies purified from 1 patient, rat liver showed canalicular IgG staining that was absent after perfusion with control IgG. Conclusions: PFIC-2 patients carrying severe BSEP mutations are at risk of developing BSEP antibodies post-OLT. The antibody response is polyclonal, targeting both extra- and intracellular BSEP domains. ECL1, a unique domain of BSEP, likely is a critical target involved in transport inhibition as demonstrated in several patients with AIBD manifest as cholestasis. (Hepatology 2016;63:524-537)
First published: 30 October 2015
Gesehen am 15.05.2020